Estudo comparativo do princípio da concentração no Código Orgânico Geral dos Processos do Equador e no Código Geral do Processo de Uruguai - Guevara Ruiz, Santiago Danilo (2021)
The Concentration Principle undoubtedly constitutes one of the most relevant procedural principles in any legal system. It brings speed, agility to the processes, without losing efficacy and validity in the procedural acts, which are achieved in a single moment. In Ecuador, although the 2008 Constitution establishes this principle, the current General Organic Code of Processes (COGEP) does not expressly establish it, contrary to Uruguayan procedural legislation, which does define it formally in its regulations. This is the central point on which the present study focused, delimiting the insufficiency of COGEP in terms of regulation of this principle, taking Uruguayan legislation as a reference, and based on this, a pertinent reform was proposed.